Characteristic qualities affecting landed house prices - Mohamad, Muhamad Hilmi; Nawawi, Abdul Hadi; Mohd Safian, Edie Ezwan; Ahmad Saleh, Ahmad Fawwaz (e-International Publishing House, 2018)
The research was conducted to find the characteristics quality of houses in Malaysia. The aim of this research was to produce the ranking characteristics of house qualities and determining its weightages. The methodology used in this research was primarily by using the Delphi Method to ascertain characteristics quality and also Analytical Hierarchy Process to determine the ranking of the characteristics quality. Data collection gathered through a structured questionnaire that incorporates the element of Saaty’s Scale using variables outlined from review and interview. A theoretical framework of the research was established from this that will lead to future research model.